Can healthy eating be cool?: a study of celebrities’ impact on teens’ attitudes towards healthy eating - Gregório, Filipa dos Reis (2014)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics